RESERVES AND RETAINED INCOME. - Graham, Willard J.; Borth, Daniel; Hill, Thomas M.; Husband, George R.; Mackenzie, Donald H.; McMullen, Stewart Y.; Stans, Maurice H.; Blough, Carman G.; Dohr, James L.; King, Earle C.; Paton, William A. (The Accounting Review, 1951)
Abstract The article focuses on recommendations presented by the American Accounting Association's Committee on Concepts and Standards, regarding the use of term "reserve" in accounting. The committee recommended that the term reserve should not be employed in published financial statements of business corporations, appropriations of retained income should not be made or displayed in such a manner as to create misleading inferences, and the reserve section in corporate balance sheets should be eliminated and its elements exhibited as deduction-from-asset, or liability, or retained income amounts. In general usage, outside of accounting, a reserve is a fund of cash or other assets. In accounting the term has been used to caption a variety of balance sheet items including segregated retained income, segregated asset, asset valuation and asset amortization amounts, and liabilities. It has been recommended that the word reserve be restricted to captions describing appropriated retained income. The committee believes that the popular understanding of financial statements, and the thinking of the profession, would be promoted by abandoning the term.